Sports facilities : leisure and movement in urban space ([Place of publication not identifed] : Detail Business Information, 2019)
The book presents current sports buildings, which stand out for the quality of their construction, their integration into the urban context, and their objectives. Sport today means lifestyle and fun and is associated with joining an association and social inclusion as well as with individualization and health awareness. The spectrum of examples from all over Europe ranges from school gyms to urban open spaces that can be used by anyone at any time. The visibility and presence of spatial forms for activities such as skateboarding, jogging or fitness today are radically different from the gyms of the past, providing rich and aesthetic contributions to their surroundings.
Sports culture -- Trends in Sports hall construction -- Active cities -- Mixed Use -- Outdoors -- Light -- Construction -- Appendix.
Sports facilities :, Sports
Keywords: SPORTS